PERBEZAAN PENDAPAT DALAM PERKARA CABANG FIQH: ANALISIS TERHADAP PANDANGAN AL-QARADAWI - Ibrahim, Basri (Jurnal Syariah, 2010)
The objective of this article is to analyze the views of al-Qaradawi with regards to the disagreement among Muslim scholars in the fiqh divisions. In actual fact, the disagreement is not a new phenomenon but it exists since the early Islamic history. The data in this article are collected from various exegesis books, hadith and fiqh, especially in the book written by al-Qaradawi-Kayfa Nata‘amalu Ma‘a al-Turath wa al-Tamadhhub wa al-Ikhtilaf. Al-Qaradawi suggested that the difference of views in fiqh divisions, is something more inevitable and must not be rejected. More importantly, all parties possess positive attitude and master the ethics of handling disagreement in Islam, in order to uphold unity amongst the Muslims. Nevertheless, it does not prohibit any new researches in certain issues in order to find a view more aptly based on dalil and convenience to the Ummah.